Four rare harpacticoid copepods from shallow littoral habitats in South Korea - Karanovic, Tomislav (Zootaxa, 2023)
In natural sciences single observations are sometimes ignored and often excluded from datasets as outliers. Taxonomists refrain from reporting new records or describing new species after single specimens for obvious reasons of inability to explore sexual dimorphism and intraspecific variability. Here I report on four such harpacticoids from four different families, all collected from marine algal beds (0.5–1.5 m) in South Korea in 2013. Three of them are new species: Diarthrodes jindoensis sp. nov. (family Dactylopusiidae), Paralaophonte (P.) naroensis sp. nov. (family Laophontidae), and Xouthous naroensis sp. nov. (family Pseudotachidiidae). The fourth species, Delavalia oblonga (Lang, 1965) (family Miraciidae), is recorded for the first time from the Western Pacific, being described originally from California. One can only speculate about the reasons these harpacticoids were not found again after a decade of intensive fieldwork all around Korea, but not reporting them would be a misrepresentation of biodiversity.